Persistent Sub Macular Fluid Accumulation After Retinal Detachment Surgery: A Case Report: Poster Presentation - Case Report - Resident - ANASARY, A. A. AYU PUTRI PREMATURA SRI; Andayani, Ari (Majalah Oftalmologi Indonesia, 2023)
Introduction : Rhegmatogenous retinal detachment (RRD) is a common cause of visual impairments, with main treatment is a surgical reattachment. Persistent submacular fluid (SMF) can be found, even after ophthalmic confirmation that the retina has reattached and all retinal breaks have sealed. This condition can cause visual impairment and delay in visual recovery. Case Illustration : A 37-year-old female complained of blurred vision in her left eye for a week, with a history of LASIK four years ago in both eyes. On examination, left eye visual acuity (VA) was 6/9.5 with retinal detachment at 11 – 6 o’clock directions and break in 1 o’clock directions. The patient planned to undergo pars plana vitrectomy (PPV). The next day found the VA was 1/300. One month later, the VA was 6/6, but she felt glare and blurred when seeing a near object. Optical coherence tomography (OCT) was conducted and found a submacular fluid one month after the operation that persist two months after surgery. Discussion : Persistent SMF is mostly founds in RRD and treated by scleral buckle, rather than in patients treated with PPV. Other factors that can affect the incidence and delayed absorption is young age and macular status of retinal detachment. Uninvolved macular detachment shows no persistent SMF after PPV, a partly detached macula has a higher incidence of SMF than a detached macula after PPV. SMF is associated with poor initial visual outcome and visual improvement in its resolution. Conclusion : It remains unclear whether the final VA is affected by the persistent SMF or not.